Cognitive behaviour therapy as an evidence-based intervention for opioid use disorder: a systematic review - Shahzadi, Mafia; Bhati, Khalid Mahmood (Journal of the Pakistan Medical Association, 2024)
Objective: To explore the effectiveness of cognitive behaviour therapy as an evidence-based intervention for patients with opioid use disorder and to estimate the effect of cognitive behaviour therapy in mental health care settings. Method: The systematic review was conducted from January to April 2023, and comprised search on Web of Science, PsycINFO, Medline, Embase, Google Scholar, Science Direct, PubMed, ClinicalTrials and OvidSP databases for experimental studies and randomised controlled trials related to opioid use disorders published in peer-reviewed English-language journals between December 2022 and April 2023. The studies’ quality was assessed using the Modified Cochrane Collaboration risk of the bias assessment criteria. Results: Of the 314 studies initially identified, 42(13%) were subjected to full-text assessment, and 10(23.8%) were analysed. There were 5(50%) studies done in the United States, 2(20%) in Iran, and 1(10%) each in Germany, China and England. All 10(100%) studies were randomised controlled trials with intervention-based cognitive behaviour therapy, and reported significant results in patients diagnosed with opioid use disorders. Conclusion: All the studies analysed were heterogeneous. Cognitive behaviour therapy had a short-term impact and remained influential in the long term as well in handling cognitive and behaviour setbacks among patients with opioid use disorders. Key Words: Cognitive behaviour therapy, Opioid use disorders, Patients, Mental health, Randomised controlled trials.